Evolution of ethics in clinical research and ethics committee - Nilay Kanti Das; Amrita Sil (Wolters Kluwer Medknow Publications, 2017)
Ethics are the moral values of human behavior and the principles which govern these values. The situation becomes challenging for a doctor when he assumes the role of researcher. The doctor-researcher has to serve both the roles and at times the zeal of an investigator has the potential to cloud the morality of the physician inside. It is very important to realize that exploiting the faith of patients is an offence that tantamount to a crime. Medical science is one discipline where the advancement of knowledge is hugely guided by research and mankind has benefitted from many experiments. However benefit and risk are the two faces of the same coin. Various unethical human experiments made us realize that the whims of researchers need to be reined and led to the evolution of the first guidelines for researcher, the Nuremberg code. Thereafter the Good Clinical Practice guidelines serve as the guiding doctrine of clinical research. The principles of ethics rest on the four pillars of autonomy, beneficence, justice, non-maleficence and recently two more pillars are added which includes, confidentiality and honesty. Ethics committees serve as a guardian of these principles. The multidisciplinary Ethics Committee ensures a competent review of the ethical aspects of the project proposal submitted and does it free from any bias or external influence. Ethical review of clinical trial applications follows a decentralized process in India, and requires Ethics Committee approval for each trial site. All Ethics committees have to be registered with Drug Controller General of India (DCGI) without which they cannot approve any clinical trial protocol and has come into effect from 25th February 2013.